CÁC ĐỨT GÃY Á KINH TUYẾN HOẠT ĐỘNG TRONG PLIOCEN - ĐỆ TỨ TẠI ĐÔNG BẮC VIỆT NAM - Hải, Hạ Văn (Vietnam Journal of Earth Sciences, 2005)
This paper presents some new results about the recent activities of sub - meridional tectonic faults in the Northeastern of Vietnam. The results of remote sensing method allowed to find 4 systems of line structures in Northeastern of Vietnam . They are Northwestern - Southeastern, Northeastern - Southwestern, sub - meridional and sub -longitudinal structures. These line structures are displayed on many kinds of data, such as geophysical, earthquake, geomorphological, so they must be geological structures. They are tectonical faults. The sub- meridional fault systems were strongly active in the Pliocene to Quaternary period. Studying these faults plays an important role in the mineral exploration, construction , and environment activities. These faults are the recent active faults, so their activities have a great influence on geologic environment. Many geological disasters are closely related to these active faults.